MULTICULTURAL PAI LEARNING BASED ON ISLAMIC BOARDING SCHOOL WISDOM - Dyah Ayu Ratna Dewi A.A. (Universitas Islam Malang, 2022)
Multicultural PAI learning at SMPN 2 Paciran has a distinction with other educational institutions considering that there is a strong element of pesantren wisdom and culture. This is indicated by the addition of several subjects based on the pesantren curriculum of pesantren wisdom which continue to be cultivated in daily interactions in the SMPN 2 Paciran environment. Multicultural PAI learning at SMPN 2 Paciran Lamongan in addition to leading to the learning domain, also tries to shape students into better characters based on the values of pesantren wisdom. The approach used in this research is qualitative and the type is a case study. Sources of data in this study can be divided into two, namely human (human) and non-human. Analysis of qualitative research data is carried out through three flows of activities that occur simultaneously in the data collection process, namely: data condensation and data presentation (data displays and conclusion drawing/verification). The results of the study stated that the planning carried out by PAI teachers could not be separated from an integrative curriculum with Islamic boarding schools. Where PAI subjects in addition to containing the wisdom of pesantren, also provide local content subjects based on pesantren such as Qur'an Hadith, SKI, Fiqh, and Aqidah Akhlak. Islamic Religious Education teachers in the learning process area are supported by other components such as good mastery of material, choice of methods, use of media, and class mastery. Even though the implementation of learning is the teacher's task, it still requires coordination and assistance from teachers and other school members. PAI teachers practice habituation and examples of Multicultural values based on Islamic boarding school wisdom. Habituation can also be found in some extra activities as well as in daily life. The example of PAI teachers that can be seen in daily life makes students have role models who are close to them. The assessment of multicultural PAI education based on pesantren wisdom uses several standards. Cognitive domains can be identified through tests conducted by the teacher. To find out the affective and psychomotor domains, PAI teachers and local content looked at student behavior in everyday life at school. In addition, students are directed to memorize several letters in the Qur'an. To add and strengthen students' cognitive domains, SMPN 2 Paciran requires students to memorize all Qur’an chapters as a graduation requirement. Keywords: Learning, Multicultural PAI, Islamic Boarding School Culture